A new species of Microlestes Schmidt-Gobel, 1846 (Coleoptera: Carabidae) Southwest of the Iberian Peninsula (Portugal) with illustrated keys for the identification of the Iberian-Balearic species - Ortuño, Vicente M.; Oliveira, Amalia Espiridião (Zootaxa, 2012)
A new species of Microlestes Schmidt-Gobel, 1846 is described from the southwest of the Iberian Peninsula, Portugal. This new species was found in the Rede Natura 2000 Serra de Monchique area (Algarve). Microlestes aljezurensis n. sp. presents three anatomical characteristics that make it a very singular species: 1) unlike other Microlestes species, it shows a pronounced sexual dimorphism in the legs in the form of dentiform processes, more or less conspicuous, in the male mesofemur, mesotibia and metatibia; 2) the last abdominal sternite shows a slight marginal notch in the male; and 3) the median lobe of the aedeagus shows a tooth on the ventral side. Comments on the ecology and distribution are presented for this species. An illustrated key to the identification of the Iberian-Balearic species, with illustrations of the genitalia and other anatomical characteristics, is also included.